Complexation: An Interesting Pathway for Combining Two APIs at the Solid State - Fucheng Leng; Oleksii Shemchuk; Koen Robeyns; Tom Leyssens (Pharmaceutics, 2022)
Combining different drugs into a single crystal form is one of the current challenges in crystal engineering, with the number of reported multi-drug solid forms remaining limited. This paper builds upon an efficient approach to combining Active Pharmaceutical Ingredients (APIs) containing carboxylic groups in their structure with APIs containing pyridine moieties. By transforming the former into their zinc salts, they can be successfully combined with the pyridine-containing APIs. This work highlights the successfulness of this approach, as well as the improvement in the physical properties of the obtained solid forms.